Eminent Domain in Nepal: A Critical Legal Analysis - Giri, Saroj Kumar (Dristikon: A Multidisciplinary Journal, 2026)
Eminent domain, which is defined as a right bestowed on the government through the constitution to expropriate private property for the purpose of public benefit with appropriate compensation, is an illustration of how the need for growth and development in society and the rights of individual's clash. The following research examines the current state of eminent domain within Nepal by considering the inadequacy of the current law in addressing these opposing issues despite the existence of provisions under article 25 of the Constitution of Nepal (2015). With respect to the use of doctrinal legal research methodology, the sources considered for this analysis include constitutional provisions, the Land Acquisition Act of 2034 B.S. (1977), cases in the Supreme Court, and human rights laws. It has been established from the above analysis that although the constitution of Nepal is well-formulated, the legal structure in place is inadequate. Comparison shows that Nepal falls far short of par with regard to global criteria like the United Nations Basic Principles on Evictions and the World Bank's Resettlement Policy. Although the Supreme Court has issued encouraging statements on procedural justice and proportionality, the role of the judicial branch continues to be hampered by outdated laws, slow procedures, and poor enforcement mechanisms. It has been found that half-hearted steps will not help. Rather, a fundamental restructuring of the legal system is required. A new law on land acquisition that clearly establishes the definition of public purpose, ensures a participatory method of valuation, requires an environmental impact assessment, and provides full-scale rehabilitation can form the foundation of development under the power of eminent domain.